me & more - Fischer, Peter; Neubauer, Susanne (Luzern : Kunstmuseum Luzern, 2003)
Abakanowicz, Magdalena ; Ali, Laylah ; Bleckner, Ross ; Gormley, Antony ; Jusidman, Yishai ; Kruger, Barbara ; Krystufek, Elke ; Lüthi, Urs ; Marusic, Tatjana ; Miao, Xiaochun ; Neto, Ernesto ; Piene, Chloe ; Smith, Kiki ; Zhang, Huan
biog., bibiog. per kunstenaar
me & more, Kunstmuseum, Luzern, 9. August - 23. November 2003
me & more, Museum of Art, Lucerne, August 9 to November 23, 2003
boek